Partisipasi Stakeholders Dalam Pengelolaan Dampak Pencemaran Sungai Jenes Surakarta - Fauziah Lusi Sasongko; Ghufronudin Ghufronudin; Nurhadi Nurhadi (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
This study aims to describe the various risks or vulnerabilities in the Jenes River riparian community and the participation of stakeholders in pollution management in the Jenes River. Selection of informants using purposive sampling. Data collection techniques with observation, interviews and documentation. Analysis with interactive and theoretical models using Ulrich Beck's risk society theory and Robert K Merton's functional structural theory. The results of the study show that the people on the Jenes River border are a risky community because they intersect with industrial areas that vulnerable to physical risks, social risks, and psychological risks. Participation by the Environment Agency, River Basin Center, Community-Based Disaster Preparedness, Kampoeng Batik Laweyan Development Forum, and Community in managing the impact of Pollution on Jenes River has been analyzed using structural-functional theory through functions and dysfunctions, showing that management flow is running according to hope, but has not resolved the problem of Pollution in the Jenes River because there are still many dysfunctions that occur in each institutional system. Thus, an effort made through this functional structure must continue to work to bridge the interests and cooperation between primary and secondary stakeholders in managing Jenes River pollution.